2016
DOI: 10.1111/dom.12831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gemigliptin, a dipeptidyl peptidase‐4 inhibitor, on lipid metabolism and endotoxemia after a high‐fat meal in patients with type 2 diabetes

Abstract: We aimed to investigate the effects of gemigliptin, a dipeptidyl peptidase-4 inhibitor, on postprandial lipoprotein levels and endotoxemia in a randomized, double-blind, placebo-controlled, crossover study. Ten people with type 2 diabetes mellitus (T2DM), inadequately controlled with oral antidiabetic medications and/or lifestyle modification, were randomized to gemigliptin or placebo for 4 weeks. At the end of each treatment phase, the study participants underwent a high-fat meal tolerance test and needle asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This study demonstrated significant apoB-48 reductions in the level of tAUC, conducted before and after 6-month treatment with a teneligliptin. So far, in patients with type 2 diabetes, significant postprandial apoB-48 reductions in AUC were reported via lipid or dietary loading after 6-week or 12-week treatment with sitagliptin [23,24], and 4-week treatment with gemigliptin [25]. It is difficult to compare these studies by absolute value because the sampling times and contents of the test meals were different.…”
Section: Reproducibility Of the Results Of Other Apob-48 Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated significant apoB-48 reductions in the level of tAUC, conducted before and after 6-month treatment with a teneligliptin. So far, in patients with type 2 diabetes, significant postprandial apoB-48 reductions in AUC were reported via lipid or dietary loading after 6-week or 12-week treatment with sitagliptin [23,24], and 4-week treatment with gemigliptin [25]. It is difficult to compare these studies by absolute value because the sampling times and contents of the test meals were different.…”
Section: Reproducibility Of the Results Of Other Apob-48 Studiesmentioning
confidence: 99%
“…Among the DPP4 inhibitors examined for effects on blood apoB-48 levels before and after lipid loading or dietary loading in type 2 DM patients, sitagliptin was reported to have effects after a 6-week treatment [23] and 12-week treatment [24]; gemigliptin was reported to have effects after a 4-week treatment [25]. There are no reports on DPP4 inhibitors' long-term effects on apo-B48 and no reports on teneligliptin pre-and post-meal apo-B48.…”
Section: Introductionmentioning
confidence: 99%
“…The class of DPP-4 inhibitors is known to be potentially associated with a beneficial effect on cholesterol levels [13, 14]. Several clinical trials have also shown that anagliptin consistently decreased serum cholesterol levels, including LDL-C, [4, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Fasting serum ApoB48 levels were significantly lower with gemigliptin than with placebo (p= 0.020). However, the plasma ApoB100 levels showed no significant difference (p= 0.734) (49). Study to evaluate cardiovascular outcomes of T2DM patientstreated with gemigliptin is still ongoing.…”
Section: ) Gemigliptinmentioning
confidence: 94%